2019
DOI: 10.1029/2018gh000179
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Spatial Variability of Climate‐Relevant Hazards and Vulnerabilities in the New England Region of the United States

Abstract: Weather and climate have substantial effects on human health. While much is known about how morbidity and mortality are affected by moderate-to-extreme heat, poor air quality, and heavy precipitation individually, less is known about the cumulative occurrence of these climatic hazards, and the extent to which they spatially overlap with community-scale vulnerabilities. Specifically, there is interest in determining whether individuals living in places with the highest exposure to multiple health hazardous clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Some of these populations are referred to as susceptible, meaning they are biologically predisposed to more severe health outcomes, while others are considered vulnerable, meaning there are societal and structural issues that place them at higher risk ( 59 ). While investigations in the heat and health literature identify ways that data source decisions can affect measures of association by changing exposure misclassification rates, results from the present study show that while different data sources may decrease levels of measurement error and minimize the impact of exposure misclassification, these changes do not occur uniformly across strata of many common environmental and community determinants of health such as race, socioeconomic status, and social vulnerability, which vary substantially over space ( 49 , 60 62 ). These factors all increase a population's vulnerability to negative health effects of climate change ( 53 , 54 , 60 , 63 – 67 ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Some of these populations are referred to as susceptible, meaning they are biologically predisposed to more severe health outcomes, while others are considered vulnerable, meaning there are societal and structural issues that place them at higher risk ( 59 ). While investigations in the heat and health literature identify ways that data source decisions can affect measures of association by changing exposure misclassification rates, results from the present study show that while different data sources may decrease levels of measurement error and minimize the impact of exposure misclassification, these changes do not occur uniformly across strata of many common environmental and community determinants of health such as race, socioeconomic status, and social vulnerability, which vary substantially over space ( 49 , 60 62 ). These factors all increase a population's vulnerability to negative health effects of climate change ( 53 , 54 , 60 , 63 – 67 ).…”
Section: Discussionmentioning
confidence: 64%
“…While investigations in the heat and health literature identify ways that data source decisions can affect measures of association by changing exposure misclassification rates, results from the present study show that while different data sources may decrease levels of measurement error and minimize the impact of exposure misclassification, these changes do not occur uniformly across strata of many common environmental and community determinants of health such as race, socioeconomic status, and social vulnerability, which vary substantially over space (49,(60)(61)(62). These factors all increase a population's vulnerability to negative health effects of climate change (53,54,60,(63)(64)(65)(66)(67). The results presented here demonstrate that the evaluated data sources and methods vary across commonly identified vulnerability factors, suggesting that different exposure data may limit the ability to detect harmful health effects of climate change in a population at higher risk.…”
Section: Discussionmentioning
confidence: 72%
“…Average ambient temperature and relative humidity on a 4 km × 4 km scale over the sampling period was calculated at the geocoded residential address at the time of each visit. 41…”
Section: Methodsmentioning
confidence: 99%
“…In additional analyses, we restricted hospitalizations to the warmer months. We chose May through September because a prior study in New England demonstrated that the frequency of days with excessive heat, heavy precipitation, and ozone and fine particulate matter extremes during these months spatially corelated with social vulnerability (36). We examined separate models for inflammatory arthritis (RA, psoriatic arthritis, ankylosing spondylitis, sacroiliitis, palindromic rheumatism, juvenile idiopathic arthritis), connective tissue disease (CTD) (SLE, Sjögren's syndrome, mixed or unspecified CTD, sarcoidosis, inflammatory myositis), vasculitis, crystalline arthritis (gout and pseudogout), and osteoarthritis.…”
Section: Significance and Innovationsmentioning
confidence: 99%